(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This study questions Turkey’s expansionist ambition in Africa, with a particular focus on the rise and decline of Turkish influence in Sub-Saharan Africa. By questioning the efficiency of Ankara’s foreign policy in Africa, the study investigates how Turkey’s diplomatic tools shape opinions, influence political decisions, and foster empathy throughout the African continent. In terms of methodology, an ethnographic study design and a narrative research approach have been used, incorporating primary data from participant observation, ground research and in-depth interviews, and secondary data obtained from documentary analysis. In doing so, the current research scrutinizes the emergence and setback of Turkish foreign policy within the broader context of global politics to give a comprehensive picture of the shifting dynamics between Turkey and its African partners. From the critical thinking standpoint, the paper assesses the inadequacies of Turkey’s anti-Western narrative employed in Africa, before discussing the failures of its ‘apparent soft power’ attempts.